Group Activities to Promote Early Rehabilitation in an Acute Psychiatric Ward: A Relationship-Based Approach Focusing on Movies. Issue 2 (3rd April 2018) - Zeppegno, Patrizia; Gramaglia, Carla; Feggi, Alessandro; Marangon, Debora; Bergamasco, Paola; Vecchi, Camilla; Girardi, Luigi; Venesia, Alessandra; Gambaro, Eleonora; Torre, Eugenio
ABSTRACT: Our Psychiatry Institute has a long-standing tradition of providing training in the importance of relational and emotional skills and helping relationships. Here we describe techniques that are routinely used on our psychiatric ward (Maggiore della Carità Hospital, Novara, Italy) to promote early rehabilitation of acute psychiatric inpatients. We focus on the Cinema group, which is typical of our approach to informal, therapeutic group activity. Targeting social and relational issues as adjunct to treatment as usual is useful in acute settings and can begin at an early stage of hospitalization. Our intervention is designed to improve patients' coping strategies, relational and communication skills, and overall quality of life.